Reinforcing the brittle resistance of high-strength concrete using agricultural waste fiber - Radwa Defalla Abdel Hafez; Ali Shubbar; Mohammed Salah Nasr; Raghda Osama Abd-Al Ftah (Sustainable Structures)
The utilization of natural fiber wastes could be an ideal way to tackle two problems. Firstly, this may be a solution to the issue of environmental challenges related to agricultural wastes. Secondly, it can potentially fix high-strength concrete's (HSC) issue of unexpected (sudden) collapse. This study looked at the results of using two different kinds of natural fiber waste in HSC. Seven HSC mixtures were manufactured; three included rice straw fibers (RSF), three contained palm leaf sheath fibers (PLSF), and one was a control mix (without fibers). In this research, the volume fractions of RSF and PLSF ranged from 1% to 3% and had an aspect ratio equal to 100. Different tests, including slump test, compressive strength, modulus of elasticity, flexural strength and tensile strength were conducted to determine their various properties. There were no significant improvements on compressive strength due to use of natural fiber while its tensile and flexural strengths increased particularly when including 1% RSF. RSF improved the properties of HSC more significantly than PLSF.